Design and implementation of a single-phase inverter - Lim, Tau Wan (Nanyang Technological University, 2020)
The report presents the design and implementations of the single-phase buck and boost inverters. The buck inverter gives an output voltage lower than the input voltage while the boost inverter gives a larger output voltage than the input voltage. The inverters are designed to convert the DC supply to generate an AC sinusoidal output voltage at desired frequency level. Experimental results are presented to demonstrate the performances of the inverters.